2020
DOI: 10.1504/ijlsm.2020.103863
|View full text |Cite
|
Sign up to set email alerts
|

Reverse logistics practices in Indian pharmaceutical supply chains: a study of manufacturers

Abstract: The era of integration and globalisation forces one not to believe in a 'zero sum game'. Under the challenges like constantly increasing customers' expectations, fierce competition, high product variety, etc., winning the customers' delight and recapturing the value by their efficient reverse logistics process becomes inevitable. Such provision becomes of utmost importance when it is related with costly and health and/or life affecting products like medicines. Using suitable statistical tests, the data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Therefore, the favourable constructs of RL and the resource allotment in achieving better performance are given lesser attention. Moreover, previous studies have shown that companies are not fully motivated to follow RL programs, since they demanded additional investment and commitment (Abbas and Farooquie, 2020). After re-fabrication, the market growth contributed 10% to the overall automotive sector with less contribution from the Malaysian-based automotive industry (US ITC, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the favourable constructs of RL and the resource allotment in achieving better performance are given lesser attention. Moreover, previous studies have shown that companies are not fully motivated to follow RL programs, since they demanded additional investment and commitment (Abbas and Farooquie, 2020). After re-fabrication, the market growth contributed 10% to the overall automotive sector with less contribution from the Malaysian-based automotive industry (US ITC, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the Indian pharmaceutical industry, the continued prevalence of expired and low-quality medicines has been linked to the marketplace influx of unwanted products leading towards a negative impact on SCM as well as health hazards. Along with the reverse logistics approach in improving pricing and regulatory policies, increasing customer understanding of medicinal usage and cooperative procurement of therapeutic goods have been recognized as steps to increase competitiveness and efficiency among players and mitigate market floods with low-quality medicine (Abbas & Farooquie, 2020).…”
Section: Swot Analysismentioning
confidence: 99%
“…In other words, early studies on reverse logistics and environmental issues in PSCs have been more at the conceptual level. Abbas and Farooquie ( 2018 ) worked conceptually on returning unsold/unwanted medicines from retailers to producers. These medicines included items that either did not match prescription or they had expired.…”
Section: Literature Reviewmentioning
confidence: 99%